2015
DOI: 10.1016/j.jvs.2014.06.109
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of endovascular versus surgical revascularization for acute lower extremity ischemia

Abstract: In patients presenting with class II ALI, ER or surgical OR resulted in comparable limb salvage rates. Although technical success is higher with OR for patients presenting with failed bypass grafts, the amputation rates are comparable. Overall mortality rates are significantly higher at 30 days and 1 year in the OR group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
59
4
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 10 publications
5
59
4
6
Order By: Relevance
“…In this comprehensive multicenter registry, we found a technical failure rate of 11% among ALI patients treated with PVI, which is comparable to those previously reported 18, 20, 21. One study found a technical failure rate of 1.6%,19 but this lower rate may reflect the difference in endovascular treatment techniques used.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In this comprehensive multicenter registry, we found a technical failure rate of 11% among ALI patients treated with PVI, which is comparable to those previously reported 18, 20, 21. One study found a technical failure rate of 1.6%,19 but this lower rate may reflect the difference in endovascular treatment techniques used.…”
Section: Discussionsupporting
confidence: 86%
“…Our in‐hospital and 1‐year mortality of 4% and 15% were comparable to 3% to 4% and 14.3% to 18% presented from these single‐center studies 18, 19, 20, 21, 22. Interestingly, our 6% major amputation rate at 1 year after PVI was significantly lower than the rates of 13% to 32% as previously reported 18, 20, 21, 22. This may be because of the heterogeneity in patient selection and Rutherford class severity among the studies.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations